Effectiveness of Schema Therapy on Agreeableness and Sense of Coherence in Women with Marital Conflicts - Heybati Sadatmahale, Bourteh; Mazloum Vajari, Soheila (Psychology of Woman Journal, 2026)
Objective: The present study aimed to investigate the effectiveness of schema therapy on agreeableness and sense of coherence among women experiencing marital conflicts. Methods and Materials: This study employed a quantitative quasi-experimental design with a pretest–posttest control group. The statistical population consisted of women with marital conflicts who referred to psychological counseling centers in Rasht during 2025. Using purposive sampling, 34 participants were initially selected, and after attrition, 30 participants remained and were randomly assigned to an experimental group (n = 15) and a control group (n = 15). Inclusion criteria included willingness to participate, residency in Rasht, and age between 30 and 50 years. The experimental group received a schema therapy intervention based on Young’s model delivered in six 45-minute sessions, while the control group received no psychological intervention during the study period. Data were collected using the Kansas Marital Conflict Scale, the Agreeableness subscale of the NEO Five-Factor Inventory, and Antonovsky’s Sense of Coherence Questionnaire. Data analysis was conducted using analysis of covariance (ANCOVA) and independent samples t-tests in SPSS Version 26 after confirming statistical assumptions. Findings: Results of independent t-tests revealed statistically significant differences between experimental and control groups in posttest agreeableness and sense of coherence scores (p < .001). One-way ANCOVA results demonstrated significant effects of schema therapy on all components of sense of coherence, including comprehensibility (F = 9.80, p = .004), manageability (F = 5.54, p = .026), and meaningfulness (F = 12.25, p = .002). Additionally, schema therapy significantly increased agreeableness compared with the control condition (p < .001), indicating meaningful psychological change following intervention. Conclusion: Schema therapy was effective in improving agreeableness and strengthening sense of coherence among women with marital conflicts.